2019
DOI: 10.1093/gbe/evz002
|View full text |Cite
|
Sign up to set email alerts
|

The Chemosensory Receptor Repertoire of a True Shark Is Dominated by a Single Olfactory Receptor Family

Abstract: Throughout the animal kingdom chemical senses are one of the primary means by which organisms make sense of their environment. To achieve perception of complex chemosensory stimuli large repertoires of olfactory and gustatory receptors are employed in bony vertebrates, which are characterized by high evolutionary dynamics in receptor repertoire size and composition. However, little is known about their evolution in earlier diverging vertebrates such as cartilaginous fish, which include sharks, skates, rays, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 34 publications
2
40
2
Order By: Relevance
“…In the catshark, ciliated sensory neurons, the typical cell morphology of the main OE, are lacking, and the main receptor neurons of the olfactory mucosa of Scyliorhinus canicula are the microvillous receptor neurons and crypt neurons, whose projections show a segregated distribution in the OB (Theisen et al 1986; Ferrando et al 2009). Genomic studies indicate that VNS-specific genes are present in teleost fish (for review see: Grus and Zhang 2009), cartilaginous fish (Sharma et al 2019) and sea lamprey (Grus and Zhang 2009). In the catshark, V2R, a component of the vomeronasal signaling pathway, are the predominant chemosensory receptor family, and a small number of genes for chemosensory receptors of the main olfactory system are also present (Sharma et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the catshark, ciliated sensory neurons, the typical cell morphology of the main OE, are lacking, and the main receptor neurons of the olfactory mucosa of Scyliorhinus canicula are the microvillous receptor neurons and crypt neurons, whose projections show a segregated distribution in the OB (Theisen et al 1986; Ferrando et al 2009). Genomic studies indicate that VNS-specific genes are present in teleost fish (for review see: Grus and Zhang 2009), cartilaginous fish (Sharma et al 2019) and sea lamprey (Grus and Zhang 2009). In the catshark, V2R, a component of the vomeronasal signaling pathway, are the predominant chemosensory receptor family, and a small number of genes for chemosensory receptors of the main olfactory system are also present (Sharma et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic studies indicate that VNS-specific genes are present in teleost fish (for review see: Grus and Zhang 2009), cartilaginous fish (Sharma et al 2019) and sea lamprey (Grus and Zhang 2009). In the catshark, V2R, a component of the vomeronasal signaling pathway, are the predominant chemosensory receptor family, and a small number of genes for chemosensory receptors of the main olfactory system are also present (Sharma et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Chondrichthyes, it was observed that the sense of smell relies primarily on microvillous OSNs coupled to G α o [ 15 ]. The chemosensory receptor repertoire of cartilaginous fishes is dominated by the expanded V2R family, although there are also a few OR, TAAR and V1R genes [ 16 ]. As in teleosts, there is also the presence of crypt neuron-like cells but their exact receptor is unknown [ 17 ].…”
Section: The Olfactory Systems Of Jawed Vertebrates and Their Neural mentioning
confidence: 99%